BRAF V600E Mutations Occur in a Subset of Glomus Tumors, and Are Associated With Malignant Histologic Characteristics. (November 2017) - Karamzadeh Dashti, Nooshin; Bahrami, Armita; Lee, Seung J.; Jenkins, Sarah M.; Rodriguez, Fausto J.; Folpe, Andrew L.; Boland, Jennifer M.
Abstract : Glomus tumors are rare mesenchymal neoplasms with a phenotype akin to the modified smooth muscle cells of the glomus body. Most are benign, but rare examples show malignant histologic characteristics and aggressive behavior. We recently encountered a malignant glomus tumor with BRAF V600E mutation. We sought to study a large cohort for this mutation, with particular attention to associated malignant histologic characteristics. Tumors were classified based on WHO criteria as benign, uncertain malignant potential (glomus tumors of uncertain malignant potential—GT-UMP), or malignant. Tumors were screened for BRAF V600E by immunohistochemistry, and positive staining was evaluated further by Sanger sequencing. A total of 102 glomus tumors were included and classified as benign (57, 56%), GT-UMP (15, 15%) and malignant (30, 29%). Tumors occurred in patients aged 8 to 89.9 years (median: 50.2), without sex predilection (55% men). Most occurred in the superficial soft tissue (84%) and upper extremities (55%). Six of 95 tested cases had BRAF V600E mutation (6%), including 0 of 57 benign tumors, 3 of 14 GT-UMP (21%), and 3 of 24 malignant tumors (12%). Follow-up was obtained for 59 cases (median: 75.7 mo, range: 7.8 to 268.5). Three of 11 malignant tumors (27%) had progressive disease: 1 with metastasis to brain and heart, 1 with enlarging residual disease, and 1 with recurrence. Two of 4 GT-UMP (50%) had progressive disease: 1 with metastasis to lung, and 1 with local recurrence (50%). Three of 44 benign tumors (7%) had local recurrence. Two of 5 patients with BRAF V600E had progression, including 1 GT-UMP with local recurrence and 1 malignant tumor with enlarging residual disease. In summary, BRAF V600E mutation was detected in 6% of glomus tumors, all of which were malignant or GT-UMP. This mutation may be associated with a malignant phenotype, although study of additional cases is needed. In patients with progressive disease, BRAF could be a promising therapeutic target. Abstract : Supplemental Digital Content is available in the text.